How do people perceive flood risk? Findings from a public survey in Tuscany, Italy. Issue 1 (10th January 2021) - Zabini, Federica; Grasso, Valentina; Crisci, Alfonso; Gozzini, Bernardo
Abstract: The study of risk perception (RP) has much increased in the last years to improve flood risk management. Effective communication requires an understanding of how the risk of flooding is perceived by residents of different areas. In this work, RP is investigated through a survey involving 483 people living in Tuscany. RP was assessed through a score built on four items covering personal, residence, and sociodemographic variables concerning flood RP. Results showed that: (a) flood RP was moderate; (b) RP was positively correlated with age, higher education, proximity to a river and direct experience; (c) people who experienced floods felt themselves to be more informed and prepared; (d) subjectively perceived risk and experts' risk assessment seemed generally correlated, even if people living in areas at "high risk" tend to underestimate the actual flood risk level; (e) the majority of the respondents considered the government and themselves as equally responsible for personal preparedness; and (f) less than 20% was aware of a Local Emergency Plan. The need of focusing on people living in the riskiest areas with targeted communication campaigns on risk awareness, hazard preparedness, and other implications of the findings in terms of communication strategies are discussed.